Clinical features of persistent postural-perceptual dizziness coexisting with Meniere’s disease in comparison with Meniere’s disease alone - Yagi, Chihiro; Kimura, Akira; Ishida, Keito; Takahashi, Takeshi; Kai, Ryota; Yamagishi, Tatsuya; Oshima, Shinsuke; Izumi, Shuji; Horii, Arata (Frontiers in Neurology, 2024)
Background Persistent postural-perceptual dizziness (PPPD) is a chronic vestibular syndrome often triggered by acute or episodic vestibular syndromes, such as Meniere’s disease (MD). According to the diagnostic criteria, PPPD may coexist with other structural diseases, and the evidence of another active illness does not necessarily exclude PPPD diagnosis. However, persistent symptoms, even those meeting the PPPD criteria even long after Meniere’s attack, are often overlooked as potential PPPD precipitated by MD. Some clinicians overlook PPPD in such patients, treating them solely for MD once diagnosed. Since a treatment strategy for PPPD is completely different from that for MD, this may result in the deprivation of adequate treatments. Objectives To emphasize the importance of diagnosing PPPD coexisting with MD including not treating such patients solely for MD, and to compare the clinical features of PPPD and MD. Methods Vestibular function tests, including canal paresis (CP)%, c- and o-vestibular myogenic potentials, vestibulo-ocular reflex-direction preponderance, and posturography and clinical symptom scales, including the Dizziness Handicap Inventory, Niigata PPPD Questionnaire, and Hospital Anxiety and Depression Scale, were compared between 105 PPPD patients with MD or other precipitants and 130 patients with MD alone. The clinical symptom scales were further compared between 23 patients with PPPD coexisting with MD and those with MD alone. Results The CP% was significantly higher in patients with MD than in those with PPPD. However, the total and subscores of all three clinical symptom scales were higher in patients with PPPD than in those with MD. The total score on all clinical symptom scales was higher in patients with PPPD coexisting with MD than in those with MD alone. Conclusion Persistent postural-perceptual dizziness development from a precipitating MD may be associated with more severe clinical symptoms. Thus, clinical symptom scales may be useful for detecting PPPD in patients with Meniere’s disease.